2021
DOI: 10.21668/health.risk/2021.1.07.eng
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentration in vegetables and their potential risk for human health

Abstract: This study assesses heavy metal levels in the water, soil, and vegetables (swiss chard, lettuce, cabbage, collard green, tomato, green pepper, and carrot) irrigated with wastewater in Gamo, Ethiopia. The samples of soils, waters, and vegetables were randomly collected, processed, and analyzed for heavy metals using atomic absorption spectroscopy. The results obtained show that the mean concentrations of Cd, Cr, and Ni had the highest concentration, and Pb, Zn, and Cu had the lowest concentration in irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Another recent study reported TE (Pb, Cr, Cu, and Cd) accumulation in vegetables (cabbage, tomato, pepper, carrot, and lettuce) grown in soils of Ethiopia. The results found high mean concentrations of Cd in all vegetables within the range of 0.20-0.38 mg kg −1 [98].…”
Section: Tesmentioning
confidence: 84%
“…Another recent study reported TE (Pb, Cr, Cu, and Cd) accumulation in vegetables (cabbage, tomato, pepper, carrot, and lettuce) grown in soils of Ethiopia. The results found high mean concentrations of Cd in all vegetables within the range of 0.20-0.38 mg kg −1 [98].…”
Section: Tesmentioning
confidence: 84%
“…Once it is ingested in digestive system, it shows poisonous effects on the body as described in Figure 2. Heavy metal exposure typically follows this outline: from industries to air, soil, water, and foods, and then to people [55][56][57][58][59]. This heavy metals are existing in a amount of formats.…”
Section: Intake Of Heavy Metal In Human Body Through Vegetablesmentioning
confidence: 99%
“…The presence of heavy metals in vegetables can pose a risk to human health, especially if consumed in large quantities (Sirajo et al, 2023). Some studies have found that the concentration of heavy metals in vegetables, such as Tomatoes, lettuce, cabbage, and Onions, can exceed the recommended limits set by organizations like the World Health Organization and the Food and Agriculture Organization (Feseha et al, 2021;Jibrin et al, 2022). However, it is important to note that not all vegetables are equally affected, and the levels of heavy metals contamination can vary depending on the region and farming practices (Ara and Bhatti, 2015).…”
Section: Introductionmentioning
confidence: 99%